Measurement of technical efficiency m cultured carp production - frontier function approach - Jayaraman, R (Indian Journal of Fisheries, 2011)
In the present study, the economics of carp culture was investigated in Thanjavur district, Tamil Nadu (India). Further, a model to measure technical efficiency in carp farming is also described. The study showed that the annual total cost, total income and net income per ha were Rs. 8,422, Rs. 21,256 and Rs. 12,834, respectively. The frontier analysis revealed that cultured carp production can be enhanced by all the "average farmers" through adoption of the technology followed by the "progressive farmers" and by optimal allocation of the inputs